The Effects of 2011 Revised Code of Corporate Governance on Financial Reporting Quality in Nigeria: The Role of Board of Directors and Audit Committee Members - MUSTAPHA, UMAR ALIYU; TAIB, FAUZIAH MD; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
Nigeria’s fight to enhance investors’ confidence in the environment where pervasive corruption and weak contract enforcement has led the country into instituting general and sector-specific laws to improve business transparency, accountability and unethical earnings manipulations. The 2003 Code of Corporate Governance was amongst the first attempt to induce good governance behaviour but with little progress as the country was embroiled with unethical accounting scandals involving major international companies. The revised 2011 Code of Corporate Governance shifted the full accountability responsibility to boards of directors with an increased role for the audit committee to assist directors in scrutinising financial statements. This paper examined the enhanced roles of the board of directors and the audit committee in curbing unethical earnings manipulations and enhancing the financial reporting quality. Findings suggest that the role of the board of directors has not restrained companies from engaging in earnings management although the audit committee size has contributed towards enhancing the financial reporting quality. Nigeria has adopted a rule-based approach to implementing its corporate governance and it has not been successful to induce good corporate behaviour in the absence of good check and balance mechanisms in place. The human governance perspective envisages that the true essence of good governance could be achieved by placing importance on people instead of structures. It is timely that the Nigerian authorities consider this self-regulation perspective as a way forward to promote good governance and eventually, overcome all unethical practices by the corporate managers.